2020
DOI: 10.1111/1467-8268.12476
|View full text |Cite
|
Sign up to set email alerts
|

Does trade in services improve African participation in global value chains?

Abstract: This research documents facts and offers an empirical appraisal of the contribution of trade in services for African participation in global value chains. It adopts a comparative approach among flows, service categories and positions in a global value chain, using data for a panel of 36 sub-Saharan African countries from 2000 to 2017. The empirical analysis, using generalized method of moments in system, leads to three main results on the trade in services and global value chain nexus in Africa. First, the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 68 publications
1
7
0
Order By: Relevance
“…On the contrary, increased credit appears to spur TiVA. Okah Efogo (2020b) finds similar results for financial credit when considering countries in sub-Saharan Africa. Following Levine (2005), one possible explanation is misallocation where additional credit is not directed to firms operating in GVCs.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…On the contrary, increased credit appears to spur TiVA. Okah Efogo (2020b) finds similar results for financial credit when considering countries in sub-Saharan Africa. Following Levine (2005), one possible explanation is misallocation where additional credit is not directed to firms operating in GVCs.…”
Section: Resultssupporting
confidence: 61%
“…In furtherance, a third monetary instrument linked to TiVA is access to credit. Current publications on TiVA demonstrate that financial institutions' credit has ambiguous effects (Okah Efogo, 2020a, b; Allard et al ., 2016; Gereffi and Fernandez-Stark, 2016). Regarding access to credit, a number of rigidities can distort its effectiveness on TiVA intensity in services (Galesi and Rachedi, 2019).…”
Section: A Review Of the Theoretical Literature On Monetary Policy Ef...mentioning
confidence: 99%
“…The extent to which trade facilitation can stimulate development indicators like foreign direct investment (FDI) motivated the research interest of Ibrahim and Ajide (2021), who found that FDI inflows to Africa are hindered by inefficient TF on the continent. In a similar vein, Okah Efogo (2020) observed that trade in service enhances African engagement in global value chains based on empirical analyses covering 36 economies in SSA from 2000 to 2017. Moreover, the nexus between TF and trade performance constitutes the focus of some studies, such as Fiorini and Hoekman (2018) and Lemi (2017), which lend credence to the significant effects of TF on trade performance.…”
Section: Literature Reviewmentioning
confidence: 87%
“…At the firm level, Amendolagine et al (2019) found that local sourcing promotes intense GVC participation and upstream sector participation, and the effect is more in countries with good political institutions and better education. Policy and institutions, institutional services, social network, and service trade are also identified as important drivers of GVC participation in Africa (Abdul‐Rahaman & Abdulai, 2020; Anyanwu & Kponnou, 2017; Akrong et al, 2020; Okah Efogo, 2020; Vakataki‘Ofa & Karingi, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%